MEDIA MONOPOLI EDUKATIF UNTUK SISWA SD KELAS IV PADA MATA PELAJARAN SENI BUDAYA - Safira, Alda; Hera, Treny; Gunawan, Hendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an Educational Monopoly learning media for fourth-grade elementary school students in the Arts and Culture subject, particularly on rhythm and musical instruments, that is valid, practical, and effective. The research employed a Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The participants were fourth-grade students of SD Negeri 90 Palembang. Data were collected through observations, interviews, expert validation questionnaires, student response questionnaires, and learning achievement tests. The results showed that the Educational Monopoly media achieved an average validation score of 83.60%, indicating a highly valid category. The practicality test obtained scores of 94.27% in the one-to-one evaluation and 90% in the small-group evaluation, both categorized as highly practical. Observation results revealed that student participation and motivation reached 94%, while learning achievement data indicated that most students achieved the expected mastery criteria. Therefore, the Educational Monopoly media is considered suitable for Arts and Culture learning because it enhances students’ motivation, participation, and understanding of learning materials.